Gender-based inequalities, religious extremism, and the Shakahola pandemic: exploring the intersection of women, religion and sustainable development in Kenya - Rev. Eunice Anyanje Obulemire (Pharos Journal of Theology)
The research examined the impact of women’s experiences during the Shakahola Pandemic in Kenya, based on religious institutions and beliefs in mitigating gender-based biases and violence and one of the worst mass suicides in recent memory. It employed feminist theory, liberation theory, gender and development theory to give analysis of the intersection of the pandemic, religion, gender, and development in the earth centered framework. A qualitative method was used in the data collection i.e., focus groups, discussions and interviews, which focused on how women were affected during the Shakahola pandemic and the reaction of religious leaders in Kenya. The findings included insights in the ways in which the pandemic affected women’s rights despite the fact that they are the mothers giving birth to the children dying, thus, the life that is being destroyed, the roles of religious actors in responding to the crisis, and the potential for collaboration between the government and different stakeholders in addressing the challenges are discussed. This research is relevant and the knowledge is important to policy makers, practitioners, and additionally to the researchers working in the fields of sustainable development, gender equality, and religion. The study therefore examined the intersection of these different issues, aiming to give a comprehensive understanding of the complex relationship between women, religion, and pandemics in the context of religious extremism.